Vaccination among HIV-infected, HIV-exposed uninfected and HIV-uninfected children: a systematic review and meta-analysis of evidence related to vaccine efficacy and effectiveness - Adetokunboh, Olatunji O. (Hum Vaccin Immunother, 2019)
Evidence-based approaches were used in making recommendations for vaccination against vaccine-preventable diseases for HIV-infected and HIV-exposed individuals but with limited substantiation. We conducted a systematic review and meta-analysis with randomized-controlled trials (RCTs), cohort and case–control studies that have efficacy and effectiveness of vaccines in HIV-infected and HIV-exposed children as outcomes. Web of Science, Cochrane Library, PubMed and Scopus databases were searched for articles. Efficacy of 9-valent pneumococcal conjugate vaccine (PCV9) against total vaccine serotype invasive pneumococcal disease was 32% in HIV-infected children and 78% among HIV-uninfected children. Vaccine effectiveness of Bacillus Calmette–Guérin vaccine in preventing tuberculosis in HIV-infected children was zero compared to 59% protection in HIV-unexposed children. Likewise, HIV-uninfected children have better protection against invasive Haemophilus influenzae type b disease than the HIV-infected children. Effectiveness studies of rotavirus vaccines show that HIV-exposed uninfected children have similar protection against rotavirus gastroenteritis compared to the non-exposed children. Children who are severely immunosuppressed are poorly protected against invasive pneumococcal diseases. HIV-infected children tend to have lesser vaccine protection against vaccine-preventable diseases when compared to unexposed children. HIV-infected children who are immunocompetent are more likely to have better vaccine protection against vaccine-preventable diseases than those who are immunosuppressed. The overall quality of the observational studies was very low with very little confidence in the effect estimate. The overall quality of evidence for the RCT outcomes was mainly high. This study reveals a dearth of efficacy and effectiveness studies among HIV-infected and exposed children.